SINGLE MOTHERS EMPLOYED IN THE FORMAL WORK SECTOR IN GERMANY AND SOUTH AFRICA - Raniga, Tanusha; Boecker, Michael; Mthembu, Maud (Social Work/Maatskaplike Werk, 2019)
This article seeks to disrupt the dominant discourses of victimhood related to single-mother family status. Drawing on a sustainable livelihood framework, we present data from in-depth interviews held with 25 single mothers sampled in Hagen, Germany, and in Gauteng and KwaZulu-Natal provinces in South Africa. We discuss how participants engaged in positive human capital development, building social capital and tapped into multiple income streams for economic security. Given the intersectional injustices that single mothers face, the strengths the women drew on in their lives is worth noting. We conclude that single mothers have created a new narrative for themselves beyond a pathological one